Unleashing Community Empowerment through A New Regional Autonomy Concept in the 2024 Elections - Owen Main Podger (Universitas Brawijaya, 2023)
Long-term planning in all regions in Indonesia in 2025 provides a powerful opportunity to commit governments to community empowerment, an opportunity dependent on the intention of those who are elected to power in the 2024 elections, and their commitment to stress sustainable economic development in those long-term plans, and the regulations to implement the plan. As the culture of reglomania (gila peraturan) is a key inhibiter of empowerment there is a need to change that culture to one that empowers and directs development of the green economy. This paper identifies problems with legislation, including a failure to identify the public service of creating an ordered environment for community development, including regulations for economic linkages and collaboration while providing for diversity. This leads to a reconsideration of the role of provinces, further consideration of accessibility and management of land, and integrity in government. The paper concludes with changes needed in campaigning in 2024 in order to lay the foundation for medium-term and long-term plans for building community empowerment after the elections, and provides a set of recommendations.